Developing a corporate strategy as a vital aspect of strategic management in an aviation enterprise - I. A. Zubov (Путеводитель предпринимателя)
The aviation industry, as one of the key sectors of the global economy, is subject to constant changes and challenges, demanding effective strategic decisions from companies in this sector. This article examines the key elements of organizing the process of developing corporate strategies for airlines. The paper outlines a series of organizational and managerial steps aimed at facilitating the successful execution of the established set of actions directed towards achieving the objectives of the strategic management initiative. Additionally, the article addresses the challenges that aviation enterprises may encounter during the development and implementation of their corporate strategies, including global competition, evolving regulatory requirements, and environmental considerations.